Endodontic Management of Root Perforation in a Lower Left Second Molar: Case Report (CIPEEX, 2025)
Root canal perforation is characterized by accidental or pathological communication between the canal system and periradicular tissues. It can occur during endodontic treatment or because of caries, resorption, trauma, or iatrogenic failure. It is a complication that can compromise the supporting periodontium and the tooth's prognosis. Treatment success is directly related to early diagnosis, contamination control, and the use of biocompatible materials, such as mineral trioxide aggregate (MTA), which promote tissue repair. This study reports the endodontic management of a root perforation in a mandibular left second molar, highlighting the clinical approach and the results obtained. An adult patient presented with spontaneous pain and discomfort upon chewing. Clinical examination revealed sensitivity to vertical percussion, without tooth mobility. Periapical radiography revealed a radiolucent image in the furcation region, suggestive of perforation. After anesthesia and absolute isolation, chemical-mechanical preparation was performed with 2.5% sodium hypochlorite and 17% EDTA. The perforation area was appropriately curetted and sealed with MTA, due to its sealing properties and biocompatibility. The canals were filled using a thermoplastic technique with gutta-percha and bioceramic cement. The tooth was initially restored with a provisional composite resin and subsequently with a definitive indirect restoration. A 6-month follow-up revealed no signs or symptoms, along with regression of the radiolucent image, demonstrating a satisfactory clinical outcome. It is concluded that, although root perforation has a poor prognosis, appropriate management, combined with the use of materials with biological repair potential, can preserve the function and integrity of the tooth. MTA proved effective in sealing the perforation and promoting periradicular repair.